Employee perception of performance appraisal and its relationship with organisational commitment: the case of a meat corporation in Namibia - Kaposambo, Vivian (Organisational Psychology, 2017)
Performance appraisal is a human resources function that many organisations undertake. Organisations should therefore try to understand why many often perceive their performance system to be unfair. The purpose of this study was to examine employee perception of performance appraisal and its relationship with their organisational commitment. Using a justice approach, this study considers issues regarding perceived fairness, trust, process clarity, and quality of communication regarding the performance appraisal system. Performance appraisal is a tool, which if managed well, will increase work performance. A quantitative research approach was used and a cross-sectional field survey generated the primary research data. An online survey consisting of 55 questions was e-mailed to 150 staff members who participate in the performance appraisal system at a Meat processing plant in Namibia. Regression analysis was employed to examine the relationship between employee perception of performance appraisal and organisational commitment. The results of the statistical analyses show that very weak to moderate relationships exist between organisational commitment and employees' perceptions' of performance appraisal. The results indicate that for an organisation to obtain employee commitment, the organisation should ensure that performance appraisal is a company-wide system that is well understood, fair and clearly communicated to the employees. Furthermore, managers should create an environment within the organisation to enhance employees' perceptions about the performance appraisal system.